External Mechanical Devices and Vascular Surgery for Erectile Dysfunction. Issue 11 (1st November 2016) - Trost, Landon W.; Munarriz, Ricardo; Wang, Run; Morey, Allen; Levine, Laurence
ABSTRACT: Introduction: The field of sexual medicine is continuously advancing, with novel outcomes reported on a regular basis. Given the rapid evolution, updated guidelines are essential to inform practicing clinicians on best practices. Aim: To summarize the current literature and provide clinical guidelines on penile traction therapy, vacuum erection devices, and penile revascularization. Methods: A consensus panel was held with leading sexual medicine experts during the 2015 International Consultation on Sexual Medicine (ICSM). Relevant literature was reviewed and graded based on Oxford criteria to develop evidence-based guideline and consensus statements. Main Outcome Measures: The development of clinically relevant guidelines. Results: Penile traction therapy is a viable therapy to modestly improve penile length as a primary therapy, before penile prosthesis placement in men with decreased penile length or after surgery for Peyronie's disease. It also might have a role in the acute phase of Peyronie's disease but has inconsistent outcomes in the long-term phase. Vacuum erection devices are effective in creating an erection satisfactory for intercourse, even in difficult-to-treat populations. They also might be used in the post-prostatectomy setting to maintain penile length but have insufficient evidence as a penile rehabilitation therapy. For vasculogenic erectile dysfunction, men with suspected arterial insufficiency can be evaluated with penile Duplex Doppler ultrasonography and confirmatory angiography. Penile revascularization procedures have consistently demonstrated benefits in very select patient populations; however, inadequate data exists to suggest the superiority of one technique. Men with vascular risk factors are likely poor candidates for penile revascularization, although veno-occlusive dysfunction and age are less significant. Therapies for treating primary veno-occlusive dysfunction are not recommended and should be reserved for clinical trials. Conclusions: Since the prior ICSM meeting, multiple developments have occurred in external mechanical devices and penile revascularization for the treatment of erectile and sexual dysfunction. Sexual medicine clinicians are encouraged to review and incorporate recommendations as applicable to their scope of practice.